Induction of MAP Kinase Homologues during Growth and Morphogenetic Development of Karnal Bunt (Tilletia indica) under the Influence of Host Factor(s) from Wheat Spikes - Atul K. Gupta; J. M. Seneviratne; G. K. Joshi; Anil Kumar (The Scientific World Journal)
Signaling pathways that activate different mitogen-activated protein kinases (MAPKs) in response to certain environmental conditions, play important role in mating type switching (Fus3) and pathogenicity (Pmk1) in many fungi. In order to determine the roles of such regulatory genes in Tilletia indica, the causal pathogen of Karnal bunt (KB) of wheat, semi-quantitative and quantitative RT-PCR was carried out to isolate and determine the expression of MAP kinase homologues during fungal growth and development under in vitro culture. Maximum expression of TiFus3 and TiPmk1 genes were observed at 14th and 21st days of culture and decreased thereafter. To investigate whether the fungus alters the expression levels of same kinases upon interaction with plants, cultures were treated with 1% of host factors (extracted from S-2 stage of wheat spikes). Such treatment induced the expression of MAPks in time dependent manner compared to the absence of host factors. These results suggest that host factor(s) provide certain signal(s) which activate TiFus3 and TiPmk1 during morphogenetic development of T. indica. The results also provides a clue about the role of host factors in enhancing the disease potential due to induction of MAP kinases involved in fungal development and pathogenecity.